Point of Purchase Communication - The Everyday Evolving An Empirical Analysis - Sharma, Madhuri; Babu, Dr (Gyan Management Journal, 2016)
Point of Purchase (PoPJ is the abode area a customer is about to buy the product. This is the crucial ere the actual barter takes place. It offers us a final scope to admonish or appeal espite of the huge amounts being spent by many companies on attractive point of lays, th ere lies a thorough dearth of a specified methodology or a barometer assessing-"""’—–,.— Jo[ all the types of communications happening ata shopping arcade.